The Waning of the renaissance, 1550-1640. - Bouwsma, William J. (The Yale Intellectual History of the West., 2002)
"Historians have viewed intellectual and artistic achievement as a seamless progression in a single direction, with the Renaissance, as identified by Jacob Burckhardt, as the root and foundation of modern culture. But in this new analysis William Bouwsma rethinks the accepted view, arguing that while the Renaissance had a beginning and, unquestionably, a climax, it also had an ending." "Examining the careers of the greatest figures of the age - Montaigne, Galileo, Jonson, Descartes, Hooker, Shakespeare, and Cervantes among many others - Bouwsma perceives in their work a growing sense of doubt and anxiety about the modern world. He considers first those features of modern European culture generally associated with the traditional Renaissance, features which reached their climax in the late sixteenth and early seventeenth centuries. But even as the movements of the Renaissance gathered strength, simultaneous impulses operated in a contrary direction. Bouwsma identifies a growing concern with personal identity, shifts in the interests of major thinkers, a decline in confidence about the future, and a heightening of anxiety." "Exploring the fluctuating and sometimes contradictory atmosphere in which Renaissance artists and thinkers operated, Bouwsma shows how the very liberation from old boundaries and modes of expression that characterised the Renaissance itself became increasingly stifling and destructive. By drawing attention to the waning of the Renaissance culture of freedom and creativity, Bouwsma offers a wholly new and intriguing interpretation of the place of the European Renaissance in modern culture.